Evaluation Score Math Education Game for Children Analythical Heuristic Processing Method With Construct Programming - Ariadi Retno (Universitas Negeri Semarang, 2023)
This research build application with animation web based use construct programming, where this application build education for children with math basic. In this application there are seven game level can user finished for learning, each level discuss math for knowledge basic for children. Level 1 user play additional math education, level 2 user play substraction math education, level 3 user play with math topic multiplication, level 4 user play with dividing math topic, level 5 user play to learn two dimensions of shape, level 6 user play three dimensions of shape, level 7 user play game math with telling basic. All level analyzed with system use Analythical Heuristic Processing (AHP) which influenced from few variable, that score each level, time solved game each level for user, and totaly level can be solved by user as last variable. In AHP dependency variable in application influenced result score for each user. Design character in this application use fani as woman character, design to learn math. All system in this application test form are usability for all form game level and AHP calculation in construct programming as well done.